PENYEBERANGAN METADATA (METADATA CROSSWALKS): ISAD (G), PERKA ANRI 21/2011, ISO 23801, RiC DAN DUBLIN CORE DI PERSIMPANGAN - Gani Nur Pramudyo; Nina Mayesti (Khazanah: Jurnal Pengembangan Kearsipan, 2022)
The aims of this study are to identify and describe crosswalks that perform and develop in SIKN and JIKN at National Archives of the Republic of Indonesia. This study uses a qualitative approach with a case study. Data was collected by online interviews on June-August 2021 and collecting documents. The results show that implementation and metadata development is related to international communities such as ICA and ISO. Analysis of metadata properties shows that metadata and description elements have similarity and different meanings, optional and mandatory elements, multilevel description, application profile that contains 4 ICA standards, inconsistencies metadata value, and did not use subject vocabularies and thesaurus. The metadata obstacle is the lack of archival information from SIKN, harvested archives is just an item, a method for metadata import/export performed manually thus metadata is not up to date in JIKN. Metadata crosswalks produce table of metadata mapping from ISAD (G), Regulatory chief of ANRI 21/2011, ISO 23801, and RiC to Dublin Core. They show the the similarities and differences metadata elements and description that was developing in archival tradition. The study suggests that ANRI adopt Indonesia Onesearch to develop metadata harvesting for SIKN and JIKN. Moreover, ANRI needs to create controlled vocabulary and perform certification for designing SIKN and operating JIKN